Natura Mortua : 5. Mednarodni Trienale Ekologija in Umetnost. - Fenz, Werner; Macel, Christine; Koscevic, Zelimir; Timár, Katalin; Storms, Walter; International Triennial The Ecology and The Art Maribor 1996; Umetnostna Galerija, Maribor (Maribor : Umetnostna Galerija Maribor, 1996)
Dreier, Veronika ; Feuerstein, Thomas ; Scherübel, Wilhelm ; Farell, Malachi ; Hybert, Fabrice ; Ivancic, Nina ; Vodopija, Mirjana ; Casolaro, Gea ; Melitopoulos, Angela ; Winklhofer ; Chilf, Mária ; Peto, Hunor ; Dimitrova, Iskra ; Uecker, Günther ; Grajfoner, Samuel ; Licul, Maja ; Ozbolt, Alen
Umetnostna galerija Maribor, 8.11. - 31.12.1996
kunstcatalogus